New post office, Dawson, Yukon Territory, approximately 1900. - Hegg, Eric A., 1867-1948 (1900)
Caption on image: "New post office Dawson." Original image in Hegg Album 26, page 19. Original photograph by Eric A. Hegg 898; copied by Webster and Stevens 368.A.